A comparative life cycle assessment of alternative aviation fuels - Bicer, Yusuf; Dincer, Ibrahim (INDERSCIENCE ENTERPRISES LTD, 2016)
In this study, a comparative life cycle assessment of various alternative aviation fuels is conducted with a well-to-wake approach in order to determine the overall life cycle of a passenger aircraft running on these conventional and alternative fuels. The investigated fuels include: hydrogen, ammonia, methanol and ethanol, as well as bio fuels and jet fuels. Although there are modifications required to fulfil the aviation fuel specifications for such alternative fuels, the long term viability and environmental sustainability make them attractive solutions for the future of aviation industry. The present study uses a life cycle assessment of a passenger aircraft using various alternative aviation fuels to determine the relative environmental impact of each life cycle phase. The overall life cycle emissions of an aircraft running on various aviation fuels are calculated from well-to-wake. The processes considered in the analyses include: 1) production, operation and maintenance of the aircraft, 2) construction, maintenance and disposal of the airport, 3) production, transportation and utilisation of the aviation fuel in the aircraft. The results show that hydrogen and liquefied natural gas represent more environmentally benign alternatives although fuel costs are higher compared to ammonia, jet fuel and methanol.
Keywords: aircrafts; aviation fuels; life cycle assessment; alternative fuels; energy; environmental impact; HYDROGEN FUEL; AIRCRAFT; TRANSPORT; Engineering